2015
DOI: 10.3109/0284186x.2015.1073351
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive procedures for the management of vertebral bone pain due to cancer: The EAPC recommendations

Abstract: Background: Image-guided percutaneous ablation methods have proved effective for treatment of benign bone tumors and for palliation of metastases involving the bone. However, the role of these techniques is controversial and has to be better defined in the setting of palliative care. Methods: A systematic review of the existing data regarding minimally invasive techniques for the pain management of vertebral bone metastases was performed by experts of the European Palliative Care Research Network. Results: Onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…48 Pharmacotherapies: Fifteen reviews were found synthesizing evidence on pharmacological interventions for pain, dyspnea, nausea/vomiting, and constipation, but evidence was low-to very low-quality, due to inconsistent findings across studies and a lack of pooled effect estimates. Eight reviews addressed pharmacological interventions for pain management and concluded there is limited evidence for metamizole in cancer pain, 70 methadone as a first-choice opioid for cancer pain, 76 levomepromazine for pain among palliative care patients, 89 paracetamol and morphine for pain in dementia patients, 65 and the use of bisphosphonates 68 or adjuvant analgesics 66 for relief of metastatic bone pain. One review concluded that transdermal buprenorphine and transdermal fentanyl demonstrate equivalent analgesic efficacy in patients with cancer pain but noted that long-term data are lacking, 56 and another review concluded that once-aday dexamethasone is the preferred corticosteroid for pain control among adult patients with glioma.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…48 Pharmacotherapies: Fifteen reviews were found synthesizing evidence on pharmacological interventions for pain, dyspnea, nausea/vomiting, and constipation, but evidence was low-to very low-quality, due to inconsistent findings across studies and a lack of pooled effect estimates. Eight reviews addressed pharmacological interventions for pain management and concluded there is limited evidence for metamizole in cancer pain, 70 methadone as a first-choice opioid for cancer pain, 76 levomepromazine for pain among palliative care patients, 89 paracetamol and morphine for pain in dementia patients, 65 and the use of bisphosphonates 68 or adjuvant analgesics 66 for relief of metastatic bone pain. One review concluded that transdermal buprenorphine and transdermal fentanyl demonstrate equivalent analgesic efficacy in patients with cancer pain but noted that long-term data are lacking, 56 and another review concluded that once-aday dexamethasone is the preferred corticosteroid for pain control among adult patients with glioma.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…Relevant studies show that nearly half of patients with malignant tumors will suffer from pain, and 60%-84% of patients with terminal cancer have cancer hurt, which seriously impacts the living quality of patients [ 14 ]. Hyperalgesia means that the hurt response to stimulation is higher than normal, while hyperalgesia means that stimulation generates pain that should not cause pain [ 15 ]. Clinically, it is considered that the pathological mechanism leading to bone cancer pain is complex, mainly due to the gradual growth of cancer cells in the bone marrow cavity, leading to bone destruction and the continuous release of related cytokines, nerve cell remodeling and peripheral sensitization, and the continuous transmission of pain information to the central nerve and central axis sensitization [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneity of study designs, outcomes, and populations still suggests that current literature provided inconsistent data and further studies should delineate confounding variables. In a recent document of the European Association for Palliative Care [17], these weaknesses and the low quality of study designs were confirmed. Recommendations for performing RFA are weak.…”
Section: Interventional Techniquesmentioning
confidence: 98%
“…Out of these, only KP had a recommendation in favor of performing this intervention in patients with vertebral tumors or metastases. However, the studies presented several weaknesses and low-quality of study designs, which reduced significantly the strength of recommendation [17]. In an update of that review (Nov 2018) following the same methodology [17], we identified another systematic review performed in 2014 with different characteristics and inclusion criteria, which also assessed treatment safety and effectiveness of vertebroplasty and kyphoplasty for treatment of cancer-related vertebral fractures and found only six RCTs among 150 selected studies.…”
Section: Interventional Techniquesmentioning
confidence: 99%